Quantum dot film cross-linked and coated with metal organic framework and preparation method of quantum dot film
Through the preparation method of cross-linked and coated quantum dot films with cross-linking and coated metal organic frames, the problem of cross-linking agent hindering carrier migration and poor film formation uniformity in the prior art is solved, and a quantum dot film with high stability and high quantum efficiency is achieved.
Patent Information
- Application Number
- CN202411956689.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-04-25
AI Technical Summary
In the existing colloidal quantum dot film formation technology, crosslinking agents hinder carrier migration, poor film formation uniformity, and insufficient stability, resulting in low quantum efficiency and poor working stability.
A metal organic frame cross-linked and coated quantum dot film is prepared by sintering and coating copper zinc indium sulfur colloidal quantum dots on a conductive glass FTO substrate to form a dense quantum dot film.
A high stability, high uniformity and high brightness quantum dot film is achieved, which improves the stability to water, light and heat, and enhances the fluorescence quantum yield through the fluorescence resonance energy transfer mechanism.
Smart Images

Figure CN119874206A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quantum dots, and in particular relates to a quantum dot film with high stability, high uniformity and high brightness prepared based on metal organic framework cross-linked quantum dots. Background Art
[0002] Colloidal quantum dots are a type of liquid-phase synthesized semiconductor and a new type of nanomaterial with three-dimensional charge confinement. By adjusting the size of colloidal quantum dots, the semiconductor absorption cutoff edge can be precisely controlled, thereby changing the first exciton absorption peak of colloidal quantum dots, and ultimately achieving the semiconductor characteristics of wide-spectrum absorption and narrow-band emission of colloidal quantum dots, which has commercial value in the application of photoelectric detection and display technology.
[0003] At present, the application of colloidal quantum dots in photoelectric detection and display devices requires a highly uniform and highly stable thin film preparation process. Considering that colloidal quantum dots are prepared by colloidal chemistry, the colloidal quantum dots are coated with a layer of passivating ligand groups in the solvent to be stably dispersed in a specific solvent. When the colloidal quantum dots are prepared into solid thin films, they are relatively sensitive to environmental factors such as water vapor, oxygen, light and heat due to their large specific surface area, multiple dangling bonds and low crystal formation energy. Therefore, they perform poorly in film uniformity and stability.
[0004] The existing colloidal quantum dot film-forming technology usually prepares the colloidal quantum dots into ink or slurry and directly fixes the colloidal quantum dots on a flat substrate by spin coating or inkjet printing. For example, in the inkjet printing process of quantum dot ink disclosed in CN115368778A, a low-viscosity quantum dot ink is used for inkjet printing to form a uniform quantum dot film. Another example is the quantum dot slurry solution disclosed in CN115044362A is directly spin-coated onto the target object to form a colloidal quantum dot film. However, the quantum dot films prepared by these methods usually contain chemical cross-linking agents, which easily cause the surface defect sites of the colloidal quantum dots to form carrier recombination centers and reduce the quantum efficiency. On the other hand, the quantum dot ink and slurry are prone to uneven film formation due to solvent volatilization, capillary and other phenomena during the drying process. Finally, since the quantum dots are directly exposed to the environment after film formation, there is a problem of poor stability, resulting in the need to add additional passivation processes.
[0005] In view of this, overcoming the deficiencies of existing products is an urgent problem to be solved in this technical field. Summary of the invention
[0006] (I) Purpose of the invention
[0007] In order to improve the above technical problems, the purpose of the present invention is to provide a method for preparing a highly stable quantum dot film based on metal organic framework cross-linking coating, so as to solve the problem that the cross-linking agent hinders carrier migration and the film formation uniformity is poor in the existing quantum dot film formation.
[0008] (II) Technical solution
[0009] The technical solution of the present invention to solve the above technical problems is as follows: first, a metal organic framework cross-linked coated quantum dot film is provided, comprising a conductive glass FTO substrate and a plurality of metal organic framework nanoparticles coated with copper zinc indium sulfur colloidal quantum dots, a metal organic framework film layer coated with copper zinc indium sulfur colloidal quantum dots is installed on the conductive glass FTO substrate, and the metal organic framework film layer coated with copper zinc indium sulfur colloidal quantum dots is formed by low-temperature sintering of a plurality of metal organic framework nanoparticles coated with copper zinc indium sulfur colloidal quantum dots.
[0010] Furthermore, a plurality of copper-zinc-indium-sulfur colloidal quantum dots are distributed in the metal organic framework nanoparticles coated with copper-zinc-indium-sulfur colloidal quantum dots.
[0011] The present invention also provides a method for preparing a quantum dot film cross-linked and coated with a metal organic framework, which specifically comprises the following steps:
[0012] (1) Synthesis of copper-zinc-indium-sulfur colloidal quantum dots: sulfur solution, copper source, indium source, and zinc source are mixed together and dissolved in oleylamine, vacuum degassed, and heated in a nitrogen atmosphere to obtain a copper-zinc-indium-sulfur solution; the copper-zinc-indium-sulfur solution is heated at 190-210° C. for 25-35 min, and quenched in ice water to obtain a copper-zinc-indium-sulfur colloidal quantum dot mother liquor; mercaptopropionic acid and dimethylformamide are added to the reaction mother liquor, mixed, heated in an air atmosphere, quenched in ice water, and isopropanol is added to precipitate, and finally the precipitate is dissolved in deionized water to obtain a copper-zinc-indium-sulfur colloidal quantum dot solution.
[0013] (2) Preparation of quantum dot film precursor cross-linked and coated by metal organic framework: Add dimethylformamide to the copper zinc indium sulfur colloidal quantum dot solution prepared in step (1), mix, heat, place a conductive glass FTO substrate, add a zinc source and an organic ligand aminoterephthalic acid, heat at 45-55°C for 23-25h, wash the quantum dot film precursor grown on the conductive glass FTO substrate with dimethylformamide three times, and then wash it with ethanol three times.
[0014] (3) Preparation of quantum dot film coated by metal organic framework cross-linking: Place the metal organic framework cross-linked quantum dot film precursor obtained in step (2) on a heating table, heat at 100-140° C. for 25-35 min, and sinter at low temperature to obtain a dense quantum dot film.
[0015] Furthermore, in step (1), the sulfur solution is obtained by dissolving sulfur powder in oleylamine, and the molar volume ratio of the sulfur powder and oleylamine is 1-3 mmol:3-5 mL.
[0016] Furthermore, in step (1), the copper source, indium source and zinc source are cuprous iodide, indium acetate and zinc acetate respectively, and the molar volume ratio of the copper source, indium source, zinc source, oleylamine and sulfur solution is 0.2-0.3 mmol: 0.4-0.6 mmol: 0.8-1.2 mmol: 5-7 mL: 3-5 mL.
[0017] Furthermore, in step (1), the molar volume ratio of the copper source, the indium source, the zinc source and oleylamine is 0.25 mmol: 0.5 mmol: 1 mmol: 6 mL: 4 mL.
[0018] Furthermore, in step (1), degassing is performed under vacuum at 80-100° C. for 25-35 min.
[0019] Furthermore, in step (1), the volume ratio of mercaptopropionic acid, dimethylformamide, the copper-zinc-indium-sulfur colloidal quantum dot mother liquor prepared in step (1) and isopropanol is 1-3:10-14:2:13-17.
[0020] Furthermore, in step (1), the volume ratio of mercaptopropionic acid, dimethylformamide, the copper-zinc-indium-sulfur colloidal quantum dot mother liquor prepared in step (1) and isopropanol is 2:12:2:15.
[0021] Furthermore, in step (1), heating is performed in an air atmosphere at 100-130° C. for 10-20 min.
[0022] Furthermore, in step (2), the molar volume ratio of the copper zinc indium sulfur colloidal quantum dot solution and dimethylformamide is 4-6 mL:4-6 mL.
[0023] Furthermore, in step (2), the molar volume ratio of the copper zinc indium sulfur colloidal quantum dot solution and dimethylformamide is 5 mL:5 mL.
[0024] Furthermore, in step (2), the zinc source is zinc acetate, and the molar volume ratio of the zinc source to aminoterephthalic acid is 25-75 mmol:50-150 mmol.
[0025] Furthermore, in step (2), the zinc source is zinc acetate, and the molar volume ratio of the zinc source to aminoterephthalic acid is 50 mmol:100 mmol.
[0026] Furthermore, in step (3), the heating stage is exposed to air atmosphere.
[0027] In one embodiment, a highly stable quantum dot film structure cross-linked with a metal organic framework is Figure 1As shown, from bottom to top: glass substrate, conductive FTO substrate, colloidal quantum dots and metal organic framework matrix mixed layer.
[0028] The results of the present invention show that the highly stable quantum dot film based on metal organic framework cross-linking and coating has good oxygen, water and thermal stability, and has high quantum efficiency fluorescence emission, which provides a new process method for preparing high-efficiency fluorescent and stable quantum dot films.
[0029] (III) Beneficial effects
[0030] The present invention has the following beneficial effects:
[0031] 1. The highly stable quantum dot film cross-linked and coated by the metal organic framework prepared by the present invention is a new type of semiconductor film material with good light absorption ability in the ultraviolet and visible bands. By customizing the cross-linking and coating ratio of the metal organic framework and the quantum dots, the defect passivation problem in the colloidal quantum dot film is effectively solved. The colloidal quantum dots are uniformly dispersed in the metal organic framework matrix, which greatly improves the stability of the colloidal quantum dot film to water, light and heat, making it have great application potential in universal luminescence and detection devices.
[0032] 2. The present invention provides a highly stable quantum dot film material based on metal organic framework cross-linking and coating through a solution phase cross-linking coating growth method. The film matrix is a metal organic framework main body, and colloidal quantum dots are dispersed in the matrix as guests. The visible fluorescence emission generated by the metal organic framework main body under light excitation overlaps with the absorption spectrum of the colloidal quantum dot guest. Through the fluorescence resonance energy transfer mechanism, the carrier radiation recombination generated in the colloidal quantum dots is enhanced, thereby achieving high quantum efficiency fluorescence emission. Compared with the independent colloidal quantum dot film prepared by slurry spin coating, it effectively solves the problems of poor working stability and low fluorescence quantum efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the structure of a highly stable quantum dot film based on metal organic framework cross-linking and coating of the present invention, wherein: 1. glass substrate, 2. conductive FTO substrate, 3. colloidal quantum dots, 4. metal organic framework matrix.
[0034] Figure 2 This is the SEM surface morphology of the metal organic framework cross-linked and coated highly stable quantum dot film obtained in Example 1.
[0035] Figure 3 This is a TEM surface morphology image of the metal organic framework cross-linked and coated highly stable quantum dot film obtained in Example 1.
[0036] Figure 4 It is the absorption spectra of Example 1 and Example 4 in the ultraviolet visible region.
[0037] Figure 5 The fluorescence emission diagrams of Example 1, Example 2, Example 3 and Example 4 under 350nm light excitation. DETAILED DESCRIPTION
[0038] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0039] Embodiment 1:
[0040] A highly stable quantum dot film based on metal organic framework cross-linking coating, the preparation method of which comprises the following steps:
[0041] (1) 2 mmol sulfur powder, 0.25 mmol cuprous iodide, 0.5 mmol zinc acetate, 1 mmol indium acetate and 10 mL oleylamine were mixed and placed in a 50 mL three-necked flask, degassed at 90° C. for 30 min under vacuum, and heated at 120° C. for 15 min under nitrogen atmosphere to prepare a copper indium zinc sulfur solution;
[0042] (2) heating the copper indium zinc sulfur solution obtained in step (1) at 200° C. for 30 min to perform quantum dot nucleation and growth, and then placing the three-necked flask of the reaction device in an ice water bath to quench, thereby obtaining a copper indium zinc sulfur colloidal quantum dot reaction mother solution;
[0043] (3) 2 mL of mercaptopropionic acid and 12 mL of dimethylformamide were mixed and placed in a 50 mL three-necked flask, 2 mL of the reaction mother solution prepared in step (2) was added, and the mixture was heated in an air atmosphere at 120° C. for 15 min, and then the three-necked flask of the reaction device was placed in cold water to quench, and then 15 mL of isopropanol was used for precipitation, and the obtained precipitate was dissolved in 30 mL of deionized water to obtain a copper-zinc-indium-sulfur colloidal quantum dot solution;
[0044] (4) 5 mL of the copper zinc indium sulfur colloidal quantum dot solution prepared in step (3), 5 mL of dimethylformamide, 50 mmol of zinc acetate and 100 mmol of aminoterephthalic acid were mixed evenly, placed in a 50 mL beaker, and a piece of FTO conductive glass was added as a substrate at the bottom of the beaker. The mixture was heated in an air atmosphere at 50° C. for 24 h. The quantum dot film precursor grown on the conductive glass FTO substrate was washed three times with dimethylformamide and then washed three times with ethanol.
[0045] (5) placing the metal organic framework cross-linked quantum dot film precursor obtained in step (4) on a heating table, heating at 120° C. for 30 min, and sintering at low temperature to obtain a dense metal organic framework cross-linked quantum dot film.
[0046] Embodiment 2:
[0047] A highly stable quantum dot film based on metal organic framework cross-linking coating, the preparation method of which comprises the following steps:
[0048] (1) 2 mmol sulfur powder, 0.25 mmol cuprous iodide, 0.5 mmol zinc acetate, 1 mmol indium acetate and 10 mL oleylamine were mixed and placed in a 50 mL three-necked flask, degassed at 90° C. for 30 min under vacuum, and heated at 120° C. for 15 min under nitrogen atmosphere to prepare a copper indium zinc sulfur solution;
[0049] (2) heating the copper indium zinc sulfur solution obtained in step (1) at 200° C. for 30 min to perform quantum dot nucleation and growth, and then placing the three-necked flask of the reaction device in an ice water bath to quench, thereby obtaining a copper indium zinc sulfur colloidal quantum dot reaction mother solution;
[0050] (3) 2 mL of mercaptopropionic acid and 12 mL of dimethylformamide were mixed and placed in a 50 mL three-necked flask, 2 mL of the reaction mother solution prepared in step (2) was added, and the mixture was heated in an air atmosphere at 120° C. for 15 min, and then the three-necked flask of the reaction device was placed in cold water to quench, and then 15 mL of isopropanol was used for precipitation, and the obtained precipitate was dissolved in 30 mL of deionized water to obtain a copper-zinc-indium-sulfur colloidal quantum dot solution;
[0051] (4) 5 mL of the copper zinc indium sulfur colloidal quantum dot solution prepared in step (3), 5 mL of dimethylformamide, 75 mmol of zinc acetate and 150 mmol of aminoterephthalic acid were mixed evenly, placed in a 50 mL beaker, and a piece of FTO conductive glass was added as a substrate at the bottom of the beaker. The mixture was heated in an air atmosphere at 50° C. for 24 h. The quantum dot film precursor grown on the conductive glass FTO substrate was washed three times with dimethylformamide and then washed three times with ethanol.
[0052] (5) placing the metal organic framework cross-linked quantum dot film precursor obtained in step (4) on a heating table, heating at 120° C. for 30 min, and sintering at low temperature to obtain a dense metal organic framework cross-linked quantum dot film.
[0053] Embodiment 3:
[0054] A highly stable quantum dot film based on metal organic framework cross-linking coating, the preparation method of which comprises the following steps:
[0055] (1) 2 mmol sulfur powder, 0.25 mmol cuprous iodide, 0.5 mmol zinc acetate, 1 mmol indium acetate and 10 mL oleylamine were mixed and placed in a 50 mL three-necked flask, degassed at 90° C. for 30 min under vacuum, and heated at 120° C. for 15 min under nitrogen atmosphere to prepare a copper indium zinc sulfur solution;
[0056] (2) heating the copper indium zinc sulfur solution obtained in step (1) at 200° C. for 30 min to perform quantum dot nucleation and growth, and then placing the three-necked flask of the reaction device in an ice water bath to quench, thereby obtaining a copper indium zinc sulfur colloidal quantum dot reaction mother solution;
[0057] (3) 2 mL of mercaptopropionic acid and 12 mL of dimethylformamide were mixed and placed in a 50 mL three-necked flask, 2 mL of the reaction mother solution prepared in step (2) was added, and the mixture was heated in an air atmosphere at 120° C. for 15 min, and then the three-necked flask of the reaction device was placed in cold water to quench, and then 15 mL of isopropanol was used for precipitation, and the obtained precipitate was dissolved in 30 mL of deionized water to obtain a copper-zinc-indium-sulfur colloidal quantum dot solution;
[0058] (4) 5 mL of the copper zinc indium sulfur colloidal quantum dot solution prepared in step (3), 5 mL of dimethylformamide, 25 mmol of zinc acetate and 50 mmol of aminoterephthalic acid were mixed evenly, placed in a 50 mL beaker, and a piece of FTO conductive glass was added as a substrate at the bottom of the beaker. The mixture was heated in an air atmosphere at 50° C. for 24 h. The quantum dot film precursor grown on the conductive glass FTO substrate was washed three times with dimethylformamide and then washed three times with ethanol.
[0059] (5) placing the metal organic framework cross-linked quantum dot film precursor obtained in step (4) on a heating table, heating at 120° C. for 30 min, and sintering at low temperature to obtain a dense metal organic framework cross-linked quantum dot film.
[0060] Embodiment 4:
[0061] A film containing only a metal organic framework matrix, the preparation method of which comprises the following steps:
[0062] (1) 5 mL of deionized water, 5 mL of dimethylformamide, 50 mmol of zinc acetate and 100 mmol of aminoterephthalic acid were mixed evenly and placed in a 50 mL beaker. A piece of FTO conductive glass was added as a substrate at the bottom of the beaker. The mixture was heated at 50 °C in an air atmosphere for 24 h. The metal organic framework matrix film precursor grown on the conductive glass FTO substrate was washed three times with dimethylformamide and then washed three times with ethanol.
[0063] (2) placing the metal organic framework matrix film precursor obtained in step (1) on a heating table, heating it at 120° C. for 30 min, and sintering it at low temperature to obtain a metal organic framework matrix film free of colloidal quantum dots.
[0064] Comparative Example 1:
[0065] A quantum dot film prepared by spin coating, the construction method comprises the following steps:
[0066] After obtaining the copper-zinc-indium-sulfur colloidal quantum dot solution in step (3), 1 mL of the copper-zinc-indium-sulfur colloidal quantum dot solution is equally divided into 10 portions; 0.1 mL of each portion is dropped onto the FTO conductive glass substrate, and a spin coater is used to spin coat it at a speed of 1000 rpm for 20 seconds, and then it is placed on a heating table and heated at 120° C. for 30 minutes; the spin coating is repeated 10 times to obtain a quantum dot film without metal organic framework cross-linking coating.
[0067] The rest is the same as in Example 1.
[0068] Performance Testing
[0069] The morphology and roughness of the quantum dot films of Examples 1-3 and Comparative Example 1 were tested, and the results are shown in Table 1 below:
[0070] Table 1 Film roughness
[0071] Project Category thickness Centerline average roughness Example 1 1.3μm 0.08μm Example 2 1.3μm 0.09μm Example 3 1.4μm 0.08μm Comparative Example 1 1.3μm 0.2μm
[0072] It can be seen from Table 1 that, compared with the comparative example, in the thin film device of the embodiment of the present application, the quantum dot thin film cross-linked and coated by the metal organic framework has better film uniformity. Figure 2 This is a SEM surface morphology image of the metal organic framework cross-linked coated highly stable quantum dot film obtained in Example 1, from which it can be seen that the surface of the film is composed of sintered submicron particles. Figure 3 This is a TEM morphology image of the metal-organic framework cross-linked and highly stable quantum dot film obtained in Example 1. The image is a high-angle annular dark field mode image. In this mode, atoms with relatively low atomic mass are darker, and atoms with relatively high atomic mass are brighter. It can be seen that the brighter colloidal quantum dot particles are uniformly distributed in the relatively dark metal-organic framework matrix.
[0073] The ultraviolet visible absorption and photoluminescence of the films of Examples 1-4 and Comparative Example 1 were tested, and the results are shown in Table 2 below:
[0074] Table 2 Photoluminescence quantum yield and absorption cutoff edge of the film
[0075] Project Category Quantum yield Absorb Cutoff Edge Example 1 92% 705nm Example 2 86% 704nm Example 3 82% 706nm Example 4 65% 405nm Comparative Example 1 52% 706nm
[0076] As can be seen from Table 2, compared with the quantum dot film comparison example 1 prepared by directly spin-coating colloidal quantum dots, the quantum dot film examples 1-3 coated by metal organic framework cross-linking all showed a significant improvement in the photoluminescence quantum yield, achieving an increase of 50% to more than 80%, among which Example 1 after optimizing the cross-linking and coating ratio achieved a photoluminescence quantum yield of more than 90%. Figure 4 1 and 2 are absorption spectra of Example 1 and Example 4 in the ultraviolet-visible region. It can be seen from Example 4 containing only a metal organic framework matrix that the ultraviolet-visible absorption cutoff edge of the metal organic framework matrix only reaches 405 nm. Figure 5 The fluorescence emission diagrams of Examples 1-3 and 4 under 350nm light excitation are combined with the absorption spectrum and the fluorescence emission spectrum. The fluorescence emission of the metal organic framework matrix is located within the absorption spectrum range of 400 to 700nm of the colloidal quantum dots, and the fluorescence resonance energy transfer mechanism of the composite fluorescence quantum yield is enhanced. Therefore, the cross-linking coating of the metal organic framework matrix can not only isolate water and oxygen to increase stability, but also improve the fluorescence quantum yield through a unique fluorescence resonance energy transfer mechanism.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A quantum dot film cross-linked and coated with a metal organic framework, characterized in that: The invention comprises a conductive glass FTO substrate and a plurality of metal organic framework nanoparticles coated with copper zinc indium sulphide colloidal quantum dots. A metal organic framework thin film layer coated with copper zinc indium sulphide colloidal quantum dots is installed on the conductive glass FTO substrate. The metal organic framework thin film layer coated with copper zinc indium sulphide colloidal quantum dots is formed by low temperature sintering of a plurality of metal organic framework nanoparticles coated with copper zinc indium sulphide colloidal quantum dots.
2. The metal organic framework cross-linked quantum dot film according to claim 1, characterized in that: A plurality of copper-zinc-indium-sulfur colloidal quantum dots are distributed in the metal organic framework nanoparticles coated with copper-zinc-indium-sulfur colloidal quantum dots.
3. A method for preparing a quantum dot film cross-linked and coated with a metal organic framework, characterized in that: The following steps are involved: (1) Synthesis of copper-zinc-indium-sulfur colloidal quantum dots: sulfur solution, copper source, indium source, and zinc source are mixed together and dissolved in oleylamine, vacuum degassed, and heated in a nitrogen atmosphere to obtain a copper-zinc-indium-sulfur solution; the copper-zinc-indium-sulfur solution is heated at 190-210° C. for 25-35 min, and quenched in ice water to obtain a copper-zinc-indium-sulfur colloidal quantum dot mother liquor; mercaptopropionic acid and dimethylformamide are added to the reaction mother liquor, mixed, heated in an air atmosphere, quenched in ice water, and isopropanol is added for precipitation, and finally the copper-zinc-indium-sulfur colloidal quantum dot solution is dissolved and precipitated with deionized water; (2) Preparation of quantum dot film precursor cross-linked and coated by metal organic framework: dimethylformamide is added to the copper zinc indium sulfur colloidal quantum dot solution prepared in step (1), mixed, heated, placed on a conductive glass FTO substrate, zinc source and organic ligand aminoterephthalic acid are added, heated at 45-55° C. for 23-25 h, and the quantum dot film precursor grown on the conductive glass FTO substrate is washed three times with dimethylformamide and then washed three times with ethanol; (3) Preparation of quantum dot film coated by metal organic framework cross-linking: Place the metal organic framework cross-linked quantum dot film precursor obtained in step (2) on a heating table, heat at 100-140° C. for 25-35 min, and sinter at low temperature to obtain a dense quantum dot film.
4. The method for preparing a quantum dot film cross-linked and coated by a metal organic framework according to claim 3, characterized in that: In step (1), the sulfur solution is obtained by dissolving sulfur powder in oleylamine, and the molar volume ratio of the sulfur powder and oleylamine is 1-3 mmol:3-5 mL.
5. The method for preparing a quantum dot film cross-linked and coated by a metal organic framework according to claim 4, characterized in that: In step (1), the copper source, indium source and zinc source are cuprous iodide, indium acetate and zinc acetate respectively, and the molar volume ratio of the copper source, indium source, zinc source, oleylamine and sulfur solution is 0.2-0.3 mmol: 0.4-0.6 mmol: 0.8-1.2 mmol: 5-7 mL: 3-5 mL.
6. The method for preparing a quantum dot film cross-linked and coated by a metal organic framework according to claim 5, characterized in that: In step (1), the molar volume ratio of the copper source, the indium source, the zinc source and oleylamine is 0.25 mmol: 0.5 mmol: 1 mmol: 6 mL: 4 mL.
7. The method for preparing a quantum dot film cross-linked and coated by a metal organic framework according to claim 5, characterized in that: In step (1), the volume ratio of mercaptopropionic acid, dimethylformamide, the copper-zinc-indium-sulfur colloidal quantum dot mother liquor prepared in step (1) and isopropanol is 1-3:10-14:2:13-17.
8. The method for preparing a quantum dot film cross-linked and coated by a metal organic framework according to claim 7, characterized in that: The volume ratio of mercaptopropionic acid, dimethylformamide, the copper-zinc-indium-sulfur colloidal quantum dot mother liquor prepared in step (1) and isopropanol is 2:12:2:
15.
9. The method for preparing a quantum dot film cross-linked and coated by a metal organic framework according to claim 7, characterized in that: In step (2), the molar volume ratio of the copper zinc indium sulfur colloidal quantum dot solution and dimethylformamide is 4-6 mL:4-6 mL.
10. The method for preparing a quantum dot film cross-linked and coated by a metal organic framework according to claim 9, characterized in that: In step (2), the zinc source is zinc acetate, and the molar volume ratio of the zinc source to aminoterephthalic acid is 25-75 mmol:50-150 mmol.
Citation Information
Patent Citations
Colloidal quantum dot film preparation method and photoelectric detector
CN115044362A
Quantum dot ink, preparation method and application
CN115368778A